PENGARUH KECENDERUNGAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI MENGHADAPI DIGITALISASI UMKM DI BANDARLAMPUNG - Imelda Sinaga; Agnes Susana Merry Purwanti; Lydia Sumiyati Sumiyati (KRISNA: Kumpulan Riset Akuntansi, 2022)
The government is targeting MSME actors to be digitally literate to simplify their business processes. But on the other hand, MSMEs have obstacles in the low quality of human resources, less than optimal support systems, namely the availability of infrastructure, incentives, access to information, and ineffective policies and regulations that still need to be addressed in the National RPJM. For this reason, the MSME business process must be addressed, one of which is the implementation of an SIA (Accounting Information System) to face digitalization. The purpose of this study is to analyze variables that tend to implement AIS so that internal parties and stakeholders can improve and improve Information Technology (IT) owned by MSMEs in Bandarlampung. The research method used is multiple linear regression using primary data on MSMEs in Bandarlampung. The results show that the influential variable is organization readiness. This means that MSMEs are willing and ready to implement AIS for the accounting information management process but have no effect on the relative advantage variable, complexity,compatibility, top management support, employee's IT competence, competitive pressure, government support, and internal control. This is because the MSMEs and stakeholders have not been adequate in implementing SIA. After all the IT used is not ready, investment and appropriate human resources are needed, still oriented to production, not market demand so that it becomes a challenge in the government's strategic plans in the future.